Seismic Loss Estimation in Pre-1970 Residential RC Buildings: The Role of Infills and Services in Low–Mid-Rise Case Studies - Del Gaudio, Carlo; De Risi, Maria Teresa; Scala, Santa Anna; Verderame, Gerardo Mario (Frontiers in Built Environment, 2020)
The lessons learned after recent earthquakes have highlighted the key role played by infills and services in damage and loss of Reinforced Concrete (RC) buildings. Their influence in seismic performance and loss estimation of selected RC building case studies is thoroughly analyzed here. The case study selection aims to be representative of existing buildings built in Italy before 1970, and covers a different number of stories and design typologies. The seismic responses of the case-study buildings are numerically analyzed by means of non-linear static pushover analysis (PO) considering a lumped plasticity approach with a quadri-linear flexural response for beam/column elements (properly calibrated for RC elements reinforced with plain bars) and a tri-linear compressive-only axial response with diagonal concentric struts for infill panels (empirically derived from experimental data on hollow clay masonry walls). Economic loss estimation is carried out via a component-based methodology that relies on the main repairing activities and resultant costs required for the refurbishment of infills and services for different damage levels. Accordingly, a damage analysis is performed herein, given the intensity measure, based on a comparison between Interstory drift demand from PO analysis and drift-based fragility functions specific for masonry infills. Loss curves, relating the total building repair cost to peak ground acceleration (PGA), are presented and compared for the analyzed case study buildings to show their trends and quantify the incidence of infills and services with respect to the reconstruction cost. A comparison between these outcomes and those recently found in the literature emphasizes the robustness of the considered approach and the reliability of the hypotheses about damage and loss assessment.